Ekran kriminal'nykh soobshchenii . Ekran kriminal'nykh soobshchenii . Screen of Criminal Reports . Экран криминальных сообщений - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on performers of the Cinema Actors' Theater who were fired because of staff cuts, and who demanded re-employment. Передача об артистах Театра Киноактера в Москве, уволенных по сокращению штата и добивающихся восстановления.